Dynamic manipulations of interacting 1d Bose gases - Aviv, Gal (2014)
Atom chips are a great tool for creation of low dimensional magnetic trapping geometries via micro-structures on the chip surface. Such structures allow the creation of time-dependent magnetic and electric potentials with highly accurate spatial and temporal dependency.